2016
DOI: 10.1371/journal.pone.0156185
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Allergic Rhinitis, Allergic Conjunctivitis, and Eczema in Children Born to Mothers with Gum Inflammation during Pregnancy

Abstract: PurposeDespite links between maternal and child health status, evidence on the association between gum infection in pregnant mothers and childhood allergies is scarce. We aim to evaluate the risk of developing allergy in children born to periodontal mothers in a nationwide study.MethodsWe conducted a 9-year population-based, retrospective cohort study using Taiwan’s National Health Insurance database. A study cohort of 42,217 newborns born to mothers with periodontal disease during pregnancy was identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another 9-year population-based, retrospective cohort study using Taiwan's National Health Insurance database demonstrated that the overall cumulative incidence and risk of AR in children born to periodontal mothers were significantly higher than those born to non-inflammatory mothers. Gum infection in women during pregnancy is an independent risk factor for allergic diseases in children, and thus its intergenerational consequences should be considered in gestational care 46…”
Section: Risk Factors Associated With Ar Incidencementioning
confidence: 99%
“…Another 9-year population-based, retrospective cohort study using Taiwan's National Health Insurance database demonstrated that the overall cumulative incidence and risk of AR in children born to periodontal mothers were significantly higher than those born to non-inflammatory mothers. Gum infection in women during pregnancy is an independent risk factor for allergic diseases in children, and thus its intergenerational consequences should be considered in gestational care 46…”
Section: Risk Factors Associated With Ar Incidencementioning
confidence: 99%
“…Among these 19 studies, 14 studies with a total sample size of 78,426 reported evidence of infection within 2 years of age and subsequent AR in children, including 7 cohort studies [ 15 , 21 26 ], 5 cross-sectional studies [ 27 31 ] and 2 case–control studies [ 16 , 32 ]. Five studies with a total sample size of 82,256 reported evidence of infection during pregnancy and AR in offspring, including 3 cohort studies [ 33 35 ], 1 cross-sectional study [ 36 ] and 1 case–control study [ 37 ]. Except for the study of Thomson 2010 [ 21 ], the quality evaluation of all the included studies was of medium to high quality.…”
Section: Resultsmentioning
confidence: 99%